Sanksi Hukum terhadap Anggota Kepolisian yang Melakukan Pungutan Liar - I Putu Gede Budihartawan; I Ketut Sukadana; I Nyoman Gede Sugiartha (Warmadewa Press, 2020)
Illegal levies commonly known as extortion are generally carried out by unscrupulous employees from an agency and even by unscrupulous officers, including police officers. The police officers who are tasked with protecting and protecting the public should not commit such illegal payments. This deviation committed by members of the police caused problems and unrest in the community. Based on this background, this research was conducted with the aim of describing how the regulation prohibits illegal levies on members of the Indonesian police force and how the legal sanctions against members of the police who carry out illegal levies. The research method used in this study was the normative method. In this study a statutory and conceptual approach was used. Prohibition of Illegal Levies is regulated in article 6 letter W of Government Regulation No.2 of 2003. Legal sanctions against members of the police who carry illegal levies are subject to the provisions of articles 368, 378, 423 of the Criminal Code. The regulation of prohibitions and sanctions against illegal levies must be emphasized so that irresponsible persons do not cause unrest in the community.